The Rise of Large Farms in Land Abundant Countries : Do They Have A Future? - Deininger, Klaus; Byerlee, Derek (2012)
Increased levels and volatility of food prices has led to a surge of interest in large-scale agriculture and land acquisition. This creates challenges for policy makers aiming to establish a policy environment conducive to an agrarian structure to contribute to broad-based development in the long term. Based on a historical review of episodes of growth of large farms and their impact, this paper identifies factors underlying the dominance of owner-operated farm structures and ways in which these may change with development. The amount of land that could potentially be available for expansion and the level of productivity in exploiting available land resources are used to establish a country-level typology. The authors highlight that an assessment of the advantages of large operations, together with information on endowments, can provide input into strategy formulation at the country level. A review of recent cases of land acquisition reinforces the importance of the policy framework in determining outcomes. It suggests that transparency and contract enforcement, recognition of local land rights and ways in which they can be exercised, attention to employment effects and technical viability, and mechanisms to re-allocate land from unsuccessful ventures to more productive entrepreneurs are key areas warranting the attention of policy makers.